Streptococcus pneumoniae promotes migration and invasion of A549 cells in vitro by activating mTORC2/AKT through up-regulation of DDIT4 expression - Song, Xiaojie; Liu, Baohong; Zhao, Guanghui; Pu, Xiaoxin; Liu, Baoyi; Ding, Meiling; Xue, Yuwen (Frontiers in Microbiology, 2022)
Dysbiosis of the lower airway flora is associated with lung cancer, of which the relationship between Streptococcus, especially pathogenic Streptococcus pneumoniae (S. pneumoniae), and the progression of lung cancer are unclear. In this study, bronchoalveolar lavage fluid (BALF) samples were prospectively collected from patients with pulmonary nodules during diagnostic bronchoscopy, and finally included 70 patients diagnosed with primary lung cancer and 20 patients with benign pulmonary nodules as the disease control group. The differential flora was screened by 16S ribosomal RNA (rRNA) gene amplicon sequencing. The results showed that the abundance of Streptococcus in the lower airway flora of lung cancer patients was significantly increased. The in vitro infection models of A549 cells and H1299 cells exposed to S. pneumoniae was established, and the migration and invasion abilities of the two kinds of cells were enhanced. The mRNA sequencing of infected A549 cells showed that the transcriptome composition was significantly different from the control group, including the high expression of DDIT4 and the up-regulation of PI3K-Akt and other signal pathways. The results of DDIT4 loss- and gain-of-function experiments in A549 cells suggest that up-regulation of DDIT4 activates the mTORC2/Akt signaling pathway, thereby enhancing the migration and invasion of A549 cells while not affecting mTORC1. Immunofluorescence (IF) and fluorescence in situ hybridization (FISH) showed that S. pneumoniae was enriched in LUAD tissues, and DDIT4 expression was significantly higher in cancer tissues than in non-cancerous tissues. The increased expression of DDIT4 was also related to the poor prognosis of patients with lung adenocarcinoma. In summary, the data provided by this study show that S. pneumoniae enriched in the lower airway of patients with lung cancer can up-regulate DDIT4 expression and subsequently activate the mTORC2/AKT signal pathway, thereby increasing the migration and invasion abilities of A549 cells.